Foreign Direct Investment and Knowledge Diffusion in Poor Locations - Girum Abebe; Margaret McMillan; Michel Serafinelli (Institute of Labor Economics (IZA), 2020)
We use a plant level survey to identify interactions between domestic plants and foreign direct investment (FDI) in Ethiopia's manufacturing sector. One third of Ethiopian plants are linked to FDI through labor sharing, supply chains and competition. Technology upgrading most commonly occurs as a result of competition in output markets and observation and imitation of FDI in the same line of business. Other benefits include enhanced managerial practices and knowledge about exporting. Spillovers from FDI are identified by comparing changes in total factor productivity (TFP) among domestic plants in districts where a large greenfield foreign plant produces and districts where FDI in the same industry and around the same time was licensed but not yet operational. Over the four years starting with the year of the FDI opening, the TFP of domestic plants is 11 percent higher in treated districts, employment in domestic plants increases and more domestic plants open.
Keywords: F21; O18; D24; 330; Foreign Direct Investment; local economic development; productivity and technology